Role of transcription factor Sp1 and RNA binding protein HuR in the downregulation of Dr+Escherichia coli receptor protein decay accelerating factor (DAF or CD55) by nitric oxide. (2nd January 2013) - Banadakoppa, Manu; Liebenthal, Daniel; Nowak, David E.; Urvil, Petri; Yallampalli, Uma; Wilson, Gerald M.; Kishor, Aparna; Yallampalli, Chandra
<x xml:space="preserve">Abstract</x> We previously reported that nitric oxide (NO) reduces the rate of bacteremia and maternal mortality in pregnant rats with uterine infection by Escherichia coli expressing the Dr Fimbria (Dr+). The epithelial invasion of Dr+E. coli is dependent on the expression level of its cellular receptor decay accelerating factor (DAF). NO reduces the rate of bacteremia by downregulating the expression of DAF. In this study, we elucidated the role of transcription factor Sp1 and RNA binding protein HuR in the downregulation of human DAF by NO. We generated a series of deletion mutant constructs of DAF gene 5′‐untranslated region and mapped the NO‐response region upstream to the core promoter region of the DAF gene. One of the several Sp1 binding sites in the DAF 5′‐untranslated region was located within the NO‐response region. The binding of Sp1 to this site was inhibited by NO. Furthermore, NO also promoted the degradation of DAF mRNA. The 3′‐untranslated region of DAF harbors an AU‐rich element and this element destabilized the mRNA transcript. NO promoted the rapid degradation of DAF mRNA by inhibiting the binding of mRNA stabilizing protein HuR to this AU‐rich region. The inhibition of binding of HuR to the AU‐rich region was due to the S‐nitrosylation of one or more cysteine residues by NO. Thus, these data reveal the molecular mediators of transcriptional and post‐transcriptional regulation of DAF by NO with implications in pathophysiology related to DAF.